Enabling Communication between Heterogeneous Robots and Human Operators in Collaborative Missions - Sewtz, Marco; Lay, Florian Samuel; Luo, Xiaozhou; Chupin, Thibaud; Lii, Neal Yi-Sheng (2024 IEEE Aerospace Conference, 2024)
Enabling the return of human presence to the lunar surface constitutes a central objective for various space agencies. While previous lunar missions were of limited duration, the landscape is poised for significant transformation in the coming years, characterized by extended surface operations and the establishment of a permanent base near the lunar south pole. As emphasized in the National Aeronautics and Space Administration (NASA)'s technology roadmap and echoed by the European Space Agency (ESA) in its Terrae Novae 2030+ roadmap, the pivotal role of robotics is underscored for attaining a sustainable lunar base. The Surface Avatar mission, led by the German Aerospace Center (DLR) and partnered by ESA, represents a pioneering effort aimed at investigating the practical application of scalable autonomy through multi-modal tele-operation and task-oriented command protocols. This approach empowers astronauts with the capability to oversee and direct a diverse fleet of robots, each with unique functions and capabilities. Aboard the International Space Station (ISS), crew members are currently entrusted with the command of a diverse ensemble of ground-based robots, including the wheeled humanoid known as Rollin' Justin, the versatile rover Interact, the articulated arm of a lander mockup, and a small four-legged system named BERT. Nonetheless, the coexistence of multiple disparate robotic systems within the same network presents a considerable challenge in achieving sustainable development. Adapting to each system's specific requirements with every update or altering the communication infrastructure to accommodate new combinations of robots is not conducive to long-term operational efficiency. This work delves into a comprehensive and modular approach designed to mitigate these challenges by minimizing the prerequisite knowledge required for each system, offering an out-of-the-box solution for situational awareness during ongoing missions, and streamlining the integration of additional systems into the mission ...